Inactivating and mutagenic effects of gamma-radiation on the causative agent of (S. typimurium 355) paratyphoid infection in model media - Eroshov, Anatol I. (Journal of the Belarusian State University. Ecology, 2019)
It is established, that the ionizing radiation processes evoke strong mutagen action. At radiation basic sensitive structures of a cell-DNA and membranes are damaged. In culture of the irradiated cells biochemical mutants have been found. In normal conditions their growth is not found. Only entering into a nutrient medium of necessary factors of growth (a set of amino acids) has raised their survival rate, but pathogenic properties have disappeared.
Keywords: gamma-radiation; pathogen of paratyphoid infection; DNA; membranes; mutants; pathogenicity